2015
DOI: 10.1016/j.neuroscience.2015.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of temporomandibular joint input to medullary dorsal horn neurons by 5HT3 receptor antagonist in female rats

Abstract: Repeated forced swim (FS) conditioning enhances nociceptive responses to temporomandibular joint (TMJ) stimulation in male and female rats. The basis for FS-induced TMJ hyperalgesia remains unclear. To test the hypothesis that serotonin 3 receptor (5HT3R) mechanisms contribute to enhanced TMJ nociception after FS, ovariectomized female rats were treated with estradiol and subjected to FS for three days. On day 4, rats were anesthetized with isoflurane and TMJ-responsive neurons were recorded from superficial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Nociceptive transmission can be affected by psychophysical stress conditions, which can influence neural functioning with regard to pain circuits in the brain [2,3]. Prior studies have found that repeated forced swim tests (FSTs), which can induce psychophysical stress conditions, enhanced nociceptive neural excitabilities in the trigeminal subnucleus caudalis (Vc) region [4][5][6], with the Vc region being well documented as a critical area for mediating nociception in deep orofacial tissues, such as masseter muscle (MM) [7,8] and temporomandibular joints [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nociceptive transmission can be affected by psychophysical stress conditions, which can influence neural functioning with regard to pain circuits in the brain [2,3]. Prior studies have found that repeated forced swim tests (FSTs), which can induce psychophysical stress conditions, enhanced nociceptive neural excitabilities in the trigeminal subnucleus caudalis (Vc) region [4][5][6], with the Vc region being well documented as a critical area for mediating nociception in deep orofacial tissues, such as masseter muscle (MM) [7,8] and temporomandibular joints [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy of note that the above‐mentioned efficacy of 5‐HT3 receptor antagonists in various models of trigeminal nociception (see Section ) has been demonstrated mostly under conditions of sustained sensitisation of different genesis, ie under persistent state of hyperalgesia which has been successfully eliminated by setrons . However, inactivation of 5‐HT3 receptors appeared to have low efficacy in acute pain conditions .…”
Section: Discussionmentioning
confidence: 99%
“…34,35 It is worthy of note that the above-mentioned efficacy of 5-HT3 receptor antagonists in various models of trigeminal nociception (see Section 1) has been demonstrated mostly under conditions of sustained sensitisation of different genesis, ie under persistent state of hyperalgesia which has been successfully eliminated by setrons. 12,13 However, inactivation of 5-HT3 receptors appeared to have low efficacy in acute pain conditions. 9,15 Furthermore, it has been shown that 5-HT3 receptor antagonists did not substantially alter the electrically evoked responses of dorsal horn neurons, 9,36 which coincides with the results of the presented study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations